A droplet-based microfluidic approach to isolating functional bacteria from gut microbiota - Yin, Jianan; Chen, Xiuzhao; Li, Xiaobo; Kang, Guangbo; Wang, Ping; Song, Yanqing; Ijaz, Umer Zeeshan; Yin, Huabing; Huang, He (Frontiers in Cellular and Infection Microbiology, 2022)
Metabolic interactions within gut microbiota play a vital role in human health and disease. Targeting metabolically interacting bacteria could provide effective treatments; however, obtaining functional bacteria remains a significant challenge due to the complexity of gut microbiota. Here, we developed a facile droplet-based approach to isolate and enrich functional gut bacteria that could utilize metabolites from an engineered butyrate-producing bacteria (EBPB) of anti-obesity potential. This involves the high throughput formation of single-bacteria droplets, followed by culturing “droplets” on agar plates to form discrete single-cell colonies. This approach eliminates the need for sophisticated s instruments to sort droplets and thus allows the operation hosted in a traditional anaerobic chamber. In comparison to the traditional culture, the droplet-based approach obtained a community of substantially higher diversity and evenness. Using the conditioned plates containing metabolites from the EBPB supernatant, we obtained gut bacteria closely associated or interacting with the EBPB. These include anaerobic Lactobacillus and Bifidobacterium, which are often used as probiotics. The study illustrates the potential of our approach in the search for the associated bacteria within the gut microbiota and retrieving those yet-to-be cultured.